2018
DOI: 10.1002/hep4.1156
|View full text |Cite
|
Sign up to set email alerts
|

Daclatasvir and sofosbuvir treatment of decompensated liver disease or post‐liver transplant hepatitis C virus recurrence in patients with advanced liver disease/cirrhosis in a real‐world cohort

Abstract: We report the findings of an early access program providing treatment for chronic hepatitis C virus infection (any genotype) with daclatasvir and sofosbuvir with/without ribavirin to patients with Child‐Pugh class C cirrhosis or prior liver transplant recipients with recurrent hepatitis C virus infection and advanced fibrosis/cirrhosis. Patients had <12‐month life expectancies per the local investigator. Patients received daclatasvir 60 mg and sofosbuvir 400 mg once daily, with/without ribavirin, for 24 weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Liver transplant recipients with HCV recurrence obtained an SVR rate of 94% following SOF/DCV/RBV for 12 weeks. Similar results were achieved in other studies with liver transplant patients [54, 110, 162]. Efficacy rates for SOF/LDV varying from 50 to 100% were seen in HCV recurrent liver transplant recipients following the fixed-dose combination of SOF/LDV [69, 124, 146].…”
Section: Special Populationssupporting
confidence: 85%
See 2 more Smart Citations
“…Liver transplant recipients with HCV recurrence obtained an SVR rate of 94% following SOF/DCV/RBV for 12 weeks. Similar results were achieved in other studies with liver transplant patients [54, 110, 162]. Efficacy rates for SOF/LDV varying from 50 to 100% were seen in HCV recurrent liver transplant recipients following the fixed-dose combination of SOF/LDV [69, 124, 146].…”
Section: Special Populationssupporting
confidence: 85%
“…In several studies, concomitant therapy with RBV resulted, as previously described [52], in anemia and leukopenia [47, 51, 5357]. Following an AE, ≤ 7% of the patients discontinued treatment with SOF/DCV, with the exception of patients with a life expectancy of less than 12 months due to decompensated cirrhosis or recurrence of HCV following a liver transplant, in whom 10% and 18%, respectively, discontinued therapy due to an AE [54].…”
Section: Efficacy and Toxicitymentioning
confidence: 96%
See 1 more Smart Citation
“…Similar trends have also been described in the United States where the SOF/DCV combination was demonstrated to be effective in patients with advanced liver disease and post‐LT recurrence. In 77 treated patients, SVR rates varied between 84% and 96% according to baseline patient characteristics . In the HCV TARGET database, one of the most important cohorts of HCV‐treated subjects, no patient receiving SOF/DCV was included .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kwo et al . [14] also demonstrated that treatment with SOF/DCV, with or without RBV, resulted in high SVR12 rates (an overall 84%) and was generally well-tolerated in this category of patients. Moreover, Ippolito et al ., [15] reported SVR12 rates of 97.6% in patients with advanced fibrosis ( n = 575) and SVR12 rates of 93.6–100% in patients with cirrhosis ( n = 2037) and suggested that DAAs can be used in patients with advanced cirrhosis.…”
Section: Discussionmentioning
confidence: 99%